Highlighting of Fluency in Stutterers - PS, Srinivas (Journal of All India Institute of Speech and Hearing)
Attempts have been made to explain stuttering using learning principles (Wischner, 1950; Sheehan, 1958; Shoemaker, 1967; and Shames and Sherrick, 1963). There have been few studies, which have applied positive reinforcement procedures to enhance the fluency among stutterers (Richard and Mundy,1966; Leach, 1969; Bar, 1971).These studies have shown that it is possible to increase the desirable behaviour, fluency, and decrease the undesirable dysfluencies (stuttering) concomittantly. Hegde (1978), while reviewing these studies states that, ’Like most clinical studies, they lack appropriate control procedures. In addition one or other of the following features was also missing from these studies: (1) Specific description of dysfluencies and their frequencies before and after therapy; (2) Definitions of fluency; (3) Operational specification of the reinforcement procedure used; and (4) A description of the final target criterion of fluency’. In spite of these drawbacks, most of the studies that have been conducted to enhance fluency have shown that it is possible to find an increase in fluency with concomittant decrease in dysfluency.